Preservation, Utilization, and Promotion of Philippine Traditional Games of the Bachelor in Physical and Health Education Pre-Service Teachers - Janette C Magalona (Humanities, Society, and Community, 2025)
The continuous advancement and the use of technology of the present generation encourage the researcher to assess the preservation, utilization, and promotion of Philippine Traditional Games of the Bachelor in Physical and Health Education pre service teachers of PNU Visayas, Philippines. A total of 110 respondents who were enrolled for Term 1 AY year 2024-2025 answered via google form. Findings revealed that BPHE pre-service teachers have Very High level of preservation in terms of organization, relevance and accessibility of games in the curriculum. For the utilization of traditional games when grouped as to game execution and cultural celebrations are very high. For competition and tournaments its high. A very high level of promotion when grouped as to inclusion to the curriculum, students’ engagement, and cultural competency training. While high for material and resources, and partnerships with communities. Significant correlations highlighted the interdependence between preservation, utilization, and promotion. A Proposed plan encompasses workshops, quality assurance mechanisms, technology integration, curriculum development, event planning, community engagement, resource allocation, and teacher training. The budget considerations underscore the need for diverse funding sources. Recommendations to higher institutions, local communities, indigenous populations, researchers, and future researchers, emphasize active student participation, ongoing teacher training, and collaborative community engagement. The proposed plan and recommendations aim to contribute to the cultural preservation, utilization, and promotion of Philippine traditional games, fostering a more inclusive educational environment.